Not just skin – Object module and measure module in the composition of the architectural envelope - Paola Scala (Agathón)
This paper investigates the role of the module in the composition of the external envelope of buildings. The opportunity presented by the call proposed by the Agathón journal serves as a pretext to initiate a reflection that, starting from Argan’s well-known distinction between object-module and measure-module, aims to highlight the relationship that exists between how architects conceive the envelope and the spatial paradigm to which they refer. The objective of this essay is to bring the attention of designers back to the importance of reflecting on the architectural quality of the envelope and its expressive capacity of facades, especially in consideration of the current historical moment in which environmental, cultural, and economic reasons increasingly urgently demand the transition from traditional construction techniques to dry assembly systems.